Amériques transculturelles - Benessaieh, Afef (Collection Transferts culturels., 2010)
"Transculturality is a new way of viewing culture that sees cultures not as separate islands that are easily differentiated from one another, but as connected and interacting webs of meaning and practice. The Americas in particular offer many examples of transcultural identities that do not fit easily into one national or ethnic mold: Chicanos, Franco-Ontarians, Creoles, and second and third generation immigrants. From Quebec to Argentina, this volume explores these identities which create themselves in a space between sameness and difference."--Project Muse website